(untitled) (Bulletin KNOB, 2021)
In the past, country house research was mainly concerned with individual houses and gardens. Yet, as early as the seventeenth and eighteenth centuries, so many country houses were being built around the major cities that they came to define the landscape. Genuine estate landscapes took shape along several rivers (Amstel, Vecht), along the inner edge of coastal dunes, and on newly reclaimed land. In the middle of the seventeenth century, the rivers were augmented with a network of barge canals and soon they too were lined by a belt of country houses. The greatest density of country houses was to be found around Amsterdam, but other big cities in the provinces of Holland and Zeeland had their fair share as well. Access was mostly by water, but in some areas, especially in Zeeland, country roads performed this role. The majority of country houses were built on or next to a farm, which generally continued to exist and, in many cases, survived the country house. In a few areas, the evolving density of country houses has been traced in a detailed chronological record. In most cases it reveals progressive growth towards a high point in the first half of the eighteenth century, after which a gradual decline sets in. However, in a number of areas growth was much more rapid, in particular along the River Vecht. Sustained growth was followed by decline. In the final decade of the eighteenth century and the first decade of the nineteenth, large numbers of country houses were demolished and in many instances the land reverted to agriculture production. It appears that the decline set in earlier in Zeeland than in Holland, but regional differences in decline are not yet entirely clear. The second quarter of the nineteenth century saw the construction of a new generation of country houses, especially in the undulating sandy areas of the Utrechtse Heuvelrug and the southern part of the Veluwezoom, where railway lines provided access. The owners of this new crop of country houses laid out their gardens in the English landscape style. They also bought up vast, neighbouring heathlands from local councils or farmers and planted them with trees. As a result, these country houses are quite different in character from those of the earlier period. In the past the concentrations of country houses dominated the landscape and even today, wherever they have survived to a substantial degree they continue to represent an important landscape quality. As such, protection and management should not be confined to individual country houses but should extend to groups of country houses and their interrelationships (in the form of visual axes, for example). In recent years, a number of provinces have already set a good example by formulating policies for country house biotopes and linear estate landscapes.